IMPLEMENTATION OF DEVELOPMENT PLANNING NOMENCLATURE IN THE REGIONAL GOVERNMENT INFORMATION SYSTEM (SIPD) DINAS PERHUBUNGAN PROVINSI JAWA BARAT - Reni Sri Rahayu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Regional Government Information System (SIPD) represents a technological innovation developed by the government to optimize efficiency and transparency in regional financial and asset management. This research focuses on analyzing the implementation level of development planning nomenclature within SIPD, with the West Java Provincial Transportation Agency as the study subject. The research subjects encompasses the agency's organizational structure, comprising a Secretariat, 4 (four) Divisions, and 7 (seven) Technical Implementation Units (UPTD). This study adopts a qualitative descriptive methodology, utilizing primary and secondary data sources. The research findings demostrate that the West Java Provincial Transportation Agency has successfully implemented SIPD optimally in accordance with available expenditure spesifications. Moreover, the agency has effectively utilized SIPD for budget planning, facilitating the execution of strategic activities aligned with the nomenclature provided in SIPD, consistent with the Regulation of the Minister of Home Affairs Number 90 of 2019 concerning Classification, Codification and Nomenclature of Regional Development Planning and Finance that has been updated by the Decree of the Minister of Home Affairs